RECONSTRUCTION OF THE DIGITAL ECONOMY ALGORITHM FROM KHITAB WAD’I TO KHITAB TAKLIF: A PERSPECTIVE FROM JASSER AUDA’S SYSTEM THEORY - Doni Ekasaputra; Tutik Hamidah; Slamet Slamet (JURNAL HAKAM, 2026)
This article examines the reconstruction of digital economic algorithms from the category of khitab wad’i to khitab taklif through the perspective of Jasser Auda’s systems theory. The rapid expansion of digital transactions has transformed algorithms from merely technical instruments into automated decision-making systems that influence contracts, pricing, recommendations, credit scoring, and user access to economic services. This development raises a fundamental question in Islamic economic law: whether algorithms should remain understood as passive legal means or be positioned as functional extensions of human action. This study employs normative legal research with conceptual, philosophical, and maqasidi approaches. The data are derived from classical usul al-fiqh literature, Jasser Auda’s systems theory, and contemporary studies on algorithmic governance in the digital economy. The findings show that classical usul al-fiqh tends to position algorithms as wasilah or sabab, while systems theory enables a more holistic reading by connecting human intention, technological design, automated action, legal consequence, and maqasid. This article argues that algorithms in the digital economy may be reconstructed as part of fi’l al-mukallaf because their operation reflects human intention, design, and responsibility. This reconstruction contributes to the development of Islamic digital economic law by strengthening legal accountability, ethical responsibility, and maqasid-based governance in automated transactions.